Bone haemophilic pseudotumour of the ulna: A rare complication of haemophilia in a dog - Decambron, Adeline; Manassero, Mathieu; Thibaud, Jean-Laurent; Reyes-Gomez, Edouard; Viateau, Véronique (Veterinary and Comparative Orthopaedics and Traumatology, 2017)
Objectives: This case report describes for the first time a bone haemophilic pseudotumour in a dog.Case description: A seven-month-old German Shepherd male dog was presented with the complaint of a forelimb weight-bearing lameness with major swelling that expanded dramatically after fine needle aspiration. Radiographs showed a large, well-defined ulnar diaphyseal cystic-like osteolytic lesion. Based on prolonged activated partial thromboplastin time (aPTT) and low factor VIII activity, haemophilia A was diagnosed. Bone scintigraphy, computed tomography, magnetic resonance imaging, and histological findings definitely ruled out malignant neoplasia or inflammation and strongly supported a bone haemophilic pseudotumour over an aneurysmal bone cyst. Segmental ulnar resection and replacement by a polymethylmethacrylate spacer combined with perioperative bleeding management resulted in a successful outcome.Discussion: This case provided evidence that a bone haemophilic pseudotumour may be the sole presenting clinical sign of haemophilia A in dogs. Early diagnosis, based on history and magnetic resonance imaging findings, is imperative for prompt treatment leading to successful outcome. It is challenging as fine needle aspiration or biopsy is contraindicated. As described in humans, surgical excision of the lesion combined with management of severe postoperative bleeding was associated with successful outcome in the present case.Clinical significance: A bone haemophilic pseudotumour should be considered in the differential diagnosis of expanding mass associated with osteolysis, especially in young male dogs. Perioperative monitoring of the bleeding disorder and subsequent FVIII replacement therapy was of paramount importance in the present case.
Keywords: Diagnostic imaging; factor VIII; haemophilia; bone tumour; dog